A multi-directional wind based triboelectric generator with investigation of frequency effects. (March 2018) - Park, Sang-Jae; Kim, Sungho; Seol, Myeong-Lok; Jeon, Seung-Bae; Tcho, Il-Woong; Kim, Daewon; Choi, Yang-Kyu
Abstract: Wind based triboelectric generators (W-TEGs) have been actively studied because of their clean, sustainable, and semi-permanent operation. However, the charge transfer characteristics of W-TEGs have not been clearly understood so far. In this work, a multi-directional W-TEG with a single stack structure, which stably collects wind energy blowing from all directions, was demonstrated. The proposed W-TEG is composed of two metal electrodes at the top and the bottom with an intercalated polymer membrane, which is driven to alternately flip and flop between both metal electrodes by an external wind. The overall shape is square, and the polymer membrane is supported by spacers at 4 corners. Structural parameters such as the thickness of the polymer membrane, the length or width of the square device, and the height of the spacers were optimized to investigate the relation between wind frequency and the amount of transferred charge. The analyzed data were supported by numerical simulations. By providing in-depth understanding this study can contribute to the development of W-TEGs. Highlights: Omni-directional wind triboelectric generator generates the same output performance. Investigated the relation between wind frequency and the amount of transferred charge. Mechanism of the each physical parameter, COMSOL simulation was performed.